Understanding the role of tourist-oriented villages in promoting rural tourism in China: integrating rural landscapes and tourist services - Yi, Yayun; Siow, May Ling; Ibrahim, Roziya; Abdul Aziz, Faziawati (Routledge, 2024)
Rural tourism strategies in underdeveloped countries have gained significant popularity in recent years. However, the repetitive and irrational construction of tourist destinations contributes to the homogeneity of the tourism environment. Low quality in the rural landscape and tourism services could affect the attraction of tourist spots. Collaboration between rural areas and service-based tourism is essential for the development of tourist-oriented villages. This review paper aims to thoroughly analyze the relationship between rural landscapes and tourism services within tourist-oriented villages in China. It further explores how the synergistic development of these two sectors can enhance rural tourism and addresses the sustainability challenges these villages face. After analyzing the data by integrated review, it is evident that the “wisdom product” concept, which integrates a high-quality rural landscape with tourism services through cultural branding, can improve the attractiveness of tourist-oriented villages and achieve sustainable growth. By grasping this concept, rural areas can experience a revival, enabling local governments, villagers, and tourism service providers to actively participate in the long-term planning, management, and development of tourist-oriented villages, crucial for the enduring success of rural tourism initiatives in China.